Prevalence and risks associated with nondiagnosed arterial hypertension: Comparative results in two Colombian cities (2023)
Objectives: To determine the prevalence and factors associated with undiagnosed hypertension in two Colombian cities. Methods: multicentered, descriptive correlational study, with a quantitative approach, nonexperimental design, in a population of 2000 inhabitants of Santa Marta and 1000 of Bucaramanga; Blood pressure measurement was performed by using the mercury sphygmomanometer following the technique and procedures recommended by the World Health Organization. Measurements of weight and height were obtained according to the application of worldwide accepted protocols and the identification of the risk factors through an instrument previously validated by experts; bioethical criteria were respected for studies with humans. The statistical analysis was performed by using the PAST software version 3.14. Results: the prevalence of undiagnosed hypertension in Santa Marta was 6.5% and in Bucaramanga 3.4%; the factors associated in the population of Santa Marta were: family history (0.33), tobacco consumption ((0.97), alcohol use (0.20) and physical exercise (0.12) and in Bucaramanga, family history (0.95), tobacco consumption (0.73), alcohol (0.88) and absence of physical exercise (0.78), the reasons for not timely diagnosis, in both populations, were due to the absence of hypertensive signs and symptoms and periodic control of the state of health. Conclusions: the prevalence of undiagnosed arterial hypertension was higher in Santa Marta than in Bucaramanga, while the behavior of the risk factors was similar. © 2018, Universidad del Norte. All rights reserved.